Kisspeptin Protein in Seminal Plasma Is Positively Associated with Semen Quality: Results from the MARHCS Study in Chongqing, China. (9th January 2019) - Zou, Peng; Wang, Xiaogang; Chen, Qing; Yang, Huan; Zhou, Niya; Sun, Lei; Chen, Hongqiang; Liu, Jinyi; Ao, Lin; Cui, Zhihong; Cao, Jia
Abstract : Objectives . To study the associations between kisspeptin levels in seminal plasma and blood plasma and semen quality. Materials and Methods . We conducted a male reproductive health survey in June 2014. A total of 666 volunteers were recruited from colleges in Chongqing, China. All volunteers completed a questionnaire including information on domestic characteristics and some potential confounders. We tested the kisspeptin levels in both blood and seminal plasma. Total seminal kisspeptin was calculated as the concentration of kisspeptin in seminal plasma multiplied by semen volume. Semen samples were tested according to the 2010 World Health Organization's (WHO) guidelines. Spearman correlation and multivariate linear regression were used to explore the association between kisspeptin concentrations in seminal plasma and blood plasma and semen quality. Potential confounders that were adjusted for included age, abstinence time, body mass index (BMI), grade, and smoking. Results . The median of kisspeptin levels in seminal plasma was 60, 000 times higher than kisspeptin in blood plasma (28.0 × 10 6 pg/ml versus 448.9 pg/ml). Each interquartile range (IQR) of kisspeptin in seminal plasma was associated with a 4.6% (95% confidence interval [CI]: 1.6%–7.6%) increase in sperm concentration. Each IQR of total kisspeptin was associated with a 7.7% (95% CI: 4.4%–11.0%) increase in total sperm number and a 7.8% (95% CI: 4.0%–11.7%) increase in total motile sperm count. Kisspeptin levels were further classified into quartiles and Q1 was set as the reference level. Subjects in the high total kisspeptin group had 57.5% (95% CI: 33.2%–86.2%) higher total sperm number than the reference group. Conclusion . The positive association between kisspeptin levels in seminal plasma and semen quality supported an important role for the KISS1/GPR54 system in male reproductive health. Kisspeptin may be a potential marker of male reproductive health and an alternative strategy for treating infertility.